2023
DOI: 10.3390/polym15132793
|View full text |Cite
|
Sign up to set email alerts
|

Conformal Cooling Channel Design for Improving Temperature Distribution on the Cavity Surface in the Injection Molding Process

Abstract: Mold heating is an essential process in plastic injection molding. Raising the temperature of the mold before injecting liquefied plastic can ease the mold-filling process. A cooling channel can be used to transport high-temperature fluids for this purpose, such as hot water or oil. This dual purpose is a cost-effective solution for heating the mold because the target temperature is easily achieved using this method. In addition, a conformal cooling channel (CCC) can provide more efficient mold heating than a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Baris et al [ 12 ] design a plastic injection mold with conformal cooling channels by metal additive manufacturing and achieved up to 62.9 % better cooling performance with a better thermal uniformity on the mold surface. Nguyen et al [ 13 ] used the response surface methodology to design a conformal channel which provide more efficient mold heating and temperature uniform than a straight cooling channel. Li et al [ 14 ] optimized the layout of heating rods to improve temperature uniformity by coupling the RSM model with a genetic algorithm (GA) for rapid heat cycle molding (RHCM) mold.…”
Section: Introductionmentioning
confidence: 99%
“…Baris et al [ 12 ] design a plastic injection mold with conformal cooling channels by metal additive manufacturing and achieved up to 62.9 % better cooling performance with a better thermal uniformity on the mold surface. Nguyen et al [ 13 ] used the response surface methodology to design a conformal channel which provide more efficient mold heating and temperature uniform than a straight cooling channel. Li et al [ 14 ] optimized the layout of heating rods to improve temperature uniformity by coupling the RSM model with a genetic algorithm (GA) for rapid heat cycle molding (RHCM) mold.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that a 9.26% reduction in the warpage of the cup-shaped injection molded part was obtained using a CCC compared with the conventional cooling channel. Nguyen et al [ 8 ] used the response surface methodology to determine the optimum CCC shape in an injection mold. The results showed that the temperature distribution of the CCC mold surface was more uniform than that of the conventional cooling channel.…”
Section: Introductionmentioning
confidence: 99%
“…Computerized simulation has proven to be an indispensable tool for evaluating CCCs [ 3 , 4 , 5 , 6 , 7 , 8 ]. This tool enables mold designers to assess and demonstrate the advantages of adopting this injection mold design type over traditional molds with conventional cooling channels.…”
Section: Introductionmentioning
confidence: 99%
“…These platforms are purpose-built to simulate the complete injection process holistically, including its myriad variables. Moreover, they facilitate fluid dynamic computational analyses, akin to those conducted using ANSYS, all rooted in firmly established injection process boundary conditions [ 7 , 8 ]. The advantages of CCCs compared with conventional channels in injection molds are evident through both simulation tools and experimental assemblies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation